2015
DOI: 10.1542/hpeds.2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Physician-, Caregiver-, and Disease-Related Factors Associated With Readmission From a Pediatric Hospital Medicine Service

Abstract: Reliable identification of preventable pediatric readmissions using individual reviewers remains a challenge. Additional studies are needed to develop a reliable approach to identify preventable readmissions and underlying modifiable factors. A focused review of 7-day readmissions and diagnoses with high readmission rates may allow use of fewer resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 28 publications
1
47
1
Order By: Relevance
“…16 There were some other important results from this study. Echoing the findings by Wallace et al, 4 the authors found that the time to readmission was shorter for potentially preventable than for nonpotentially preventable readmissions (a median of 4 days versus 9 days). Potentially preventable readmissions were more likely to be causally related to the index hospitalization than nonpreventable readmissions.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…16 There were some other important results from this study. Echoing the findings by Wallace et al, 4 the authors found that the time to readmission was shorter for potentially preventable than for nonpotentially preventable readmissions (a median of 4 days versus 9 days). Potentially preventable readmissions were more likely to be causally related to the index hospitalization than nonpreventable readmissions.…”
mentioning
confidence: 80%
“…Yet, there is angst about the appropriateness of using readmission rates for payment given the lack of evidence regarding the potential preventability of these events. 1 -3 Previous studies have assessed the preventability of pediatric readmissions through medical record review 4,5 and through application of proprietary software to administrative data. 6 These studies yielded estimates of 20% (medical record review) and almost 50% (proprietary software) preventability.…”
mentioning
confidence: 99%
“…This is especially true in pediatric settings, where overall readmission rates are much lower than in adult settings, many readmissions are expected as part of a patient's planned course of care, and variation in readmission rates between hospitals is correlated with the percentage of patients with certain complex chronic conditions . Thus, there is increasing agreement that hospitals and external evaluators need to shift the focus from all‐cause readmissions to a reliable, consistent, and fair measure of potentially preventable readmissions . In addition to being a more useful quality metric, analyzing preventable readmissions will help hospitals focus resources on patients with potentially modifiable risk factors and develop meaningful quality‐improvement initiatives to improve inpatient care as well as the discharge process to prepare families for their transition to home …”
mentioning
confidence: 99%
“…Although previous studies have attempted to distinguish preventable from nonpreventable readmissions, many reported significant challenges in completing reviews efficiently, achieving consistency in how readmissions were classified, and attaining consensus on final determinations . Studies have also demonstrated that the algorithms some states are using to streamline preventability reviews and determine reimbursements overestimate the rate of potentially preventable readmissions …”
mentioning
confidence: 99%
“…The study by Wallace et al 16 used chart review by 3 physicians to examine the reasons for and preventability of 204 readmissions to a pediatric hospital medicine service at a large academic medical center. Using a 4-tiered readmission classification scheme, they found that most (87%) 30-day readmissions were related to the same disease processes as the index admission.…”
mentioning
confidence: 99%